Strategy For International Recognition Of Pesantren-Based Islamic University Through Increasing Reputable Scientific Publications - Maimunatun Habibah (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
This study explores international recognition strategies through increasing scientific publications by lecturers at Islamic boarding schools (pesantren)-based Islamic universities. The focus of this study is on the implementation of policies to support international recognition through scientific publications. Using a case study approach, this research explores qualitative data on institutional strategies in encouraging lecturers to publish articles in reputable journals. The study yields three findings. First, there are policies providing rewards for lecturers who publish their work, especially in Scopus/WoS-indexed journals, waiving publication fees for lecturers who publish articles in all internal journals, strengthening the capacity of journal editors, and preparing for Scopus indexing for Sinta 2-accredited journals. Second, there are punishments for permanent lecturers who do not publish any work for one semester. Third, lecturers face challenges, such as limited resources, motivation, and publishing costs. These obstacles are addressed through publication reward programs, strengthening academic culture, and institutional support oriented towards the vision of a world-class university. Furthermore, lecturers with intrinsic motivation tend to be more successful in the publication process. Institutional strategies include developing individual capacity and improving the professionalism and quality of journal management. In conclusion, a comprehensive approach based on collaboration, incentives, and recognition is key to increasing pesantren-based universities' scientific productivity and competitiveness. This research provides practical guidance for other higher education institutions in developing programs to improve scientific publications.